1978
DOI: 10.1172/jci108973
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Induced Ovarian Failure in the Rat

Abstract: A B S T R A C T The effect of ethanol feeding on ovarian function and structure in fenmale rats was studied in alcohol-fed animals, isocalorically fed controls, and two ad libitum-fed control groups. Ovarian weight was reduced by 60% in alcohol-fed animals compared with the control groups. Gross disruption of ovarian architecture was noted, characterized by the absence of any corpus hemorrhagicum and corpus albicans. Moreover, plasma levels of estradiol were significantly reduced in the alcohol-fed animals (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(31 citation statements)
references
References 43 publications
(47 reference statements)
1
27
2
1
Order By: Relevance
“…We have pre viously found a reduction in the density of platelet peripheral BZ binding sites in association with alcohol ism [Suranyi-Cadotte et al, 1988], a disorder where one often finds disturbed regulation of gonadal steroid func tion [Van Thiel et al. 1975, 1978. An inference from these findings is that a relationship may exist between the peripheral BZ binding sites and circulatory levels of gonadal hormones.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have pre viously found a reduction in the density of platelet peripheral BZ binding sites in association with alcohol ism [Suranyi-Cadotte et al, 1988], a disorder where one often finds disturbed regulation of gonadal steroid func tion [Van Thiel et al. 1975, 1978. An inference from these findings is that a relationship may exist between the peripheral BZ binding sites and circulatory levels of gonadal hormones.…”
Section: Discussionmentioning
confidence: 95%
“…Using [3H]PK 11195 as a selective ligand, previous studies have de scribed significant reductions in the density of platelet peripheral BZ binding sites in schizophrenia [Gavish et al, 1986a;Weizman et al, 1986] and anxiety disorder . In recent studies we found a sig nificant reduction in the density of platelet peripheral BZ binding sites in alcoholism [Suranyi-Cadotte et al, 1988] , a disorder which is reputedly associated with altered levels of adrenal and gonadal steroids [Van Thiel et al, 1975, 1978. …”
Section: Introductionmentioning
confidence: 92%
“…[45][46][47] In rats, chronic alcohol consumption can lead to ovarian failure. 48 If suppression of ovulation and gonadotropin levels are protective against ovarian cancer as has been hypothesized, 25,26 and if alcohol disrupts these processes, then high levels of alcohol consumption may be protective against ovarian cancer.…”
Section: Discussionmentioning
confidence: 97%
“…A tendency for an earlier onset of natural menopause can be noticed in relation to increased alcohol intake as well as the frequency of alcohol consumption. Numerous tests on animals confirm the effect of alcohol on the reproductive system (van Thiel et al 1978). Studies by van Thiel et al (1978) demonstrated that ovarian failure in female rats who were fed for 7 days with alcohol in the quantity equivalent to 36% of their daily energetic requirement was more frequent than in the group which was not fed with alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous tests on animals confirm the effect of alcohol on the reproductive system (van Thiel et al 1978). Studies by van Thiel et al (1978) demonstrated that ovarian failure in female rats who were fed for 7 days with alcohol in the quantity equivalent to 36% of their daily energetic requirement was more frequent than in the group which was not fed with alcohol. Findings presented by van Emanuele et al (2002) indicate that rats which were fed with small amounts of alcohol had an increased level of estradiol in their blood.…”
Section: Discussionmentioning
confidence: 99%